2002
DOI: 10.1080/10428190290026277
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein in Acute Myeloid Leukaemia: Therapeutic Implications of its Association With Both a Multidrug-resistant and an Apoptosis-resistant Phenotype

Abstract: P-glycoprotein (Pgp) expression is an independent prognostic factor for response to remission-induction chemotherapy in acute myeloblastic leukaemia, particularly in the elderly. There are several potential agents for modulating Pgp-mediated multi-drug resistance, such as cyclosporin A and PSC833, which are currently being evaluated in clinical trials. An alternative therapeutic strategy is to increase the use of drugs which are unaffected by Pgp. However, in this review, we explain why this may be more diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 81 publications
2
55
0
2
Order By: Relevance
“…Whatever is the exact mechanism of action of these MDR proteins (decrease of intracellular drug accumulation or attenuation of the consequences of intracellular drug accumulation), the final outcome is a resistance to chemotherapeutic drug-induced apoptosis (reviewed in Sietsma et al 36 , Pallis et al . 37 ). The present investigation illustrates for the first time the involvement of SphK1 in chemoresistance of acute myeloid leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever is the exact mechanism of action of these MDR proteins (decrease of intracellular drug accumulation or attenuation of the consequences of intracellular drug accumulation), the final outcome is a resistance to chemotherapeutic drug-induced apoptosis (reviewed in Sietsma et al 36 , Pallis et al . 37 ). The present investigation illustrates for the first time the involvement of SphK1 in chemoresistance of acute myeloid leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies have indicated that Pgp and MRPs may protect astrocytes and other cell types from apoptosis. 111,112 Nevertheless, transient inhibition of ABC transporters such as Pgp by short-term administration of inhibitors may be a useful strategy to reverse or prevent pharmacoresistance due to overexpression of such transporters.…”
Section: How Can Understanding Of Bbb Abc Transporters Be Used To Incmentioning
confidence: 99%
“…In this context, it is noteworthy that an anti-apoptotic role for ABCB1 has been demonstrated recently promoting cell survival by inhibiting caspase activation. [42][43][44][45] Physiological function of other ABC transporters in HSC. Characterization of molecules with tightly controlled expression patterns during differentiation represents an important approach to understanding the regulation of HSC commitment.…”
Section: Abc Transporter Activity As Marker Of Hematopoietic Stem Cellsmentioning
confidence: 99%